shRNA-Based Screen Identifies Endocytic Recycling Pathway Components That Act as Genetic Modifiers of Alpha-Synuclein Aggregation, Secretion and Toxicity - Gonçalves, Susana A (2016)
Alpha-Synuclein (aSyn) misfolding and aggregation is common in several neurodegenerative diseases, including Parkinson's disease and dementia with Lewy bodies, which are known as synucleinopathies. Accumulating evidence suggests that secretion and cell-to-cell trafficking of pathological forms of aSyn may explain the typical patterns of disease progression. However, the molecular mechanisms controlling aSyn aggregation and spreading of pathology are still elusive. In order to obtain unbiased information about the molecular regulators of aSyn oligomerization, we performed a microscopy-based large-scale RNAi screen in living cells. Interestingly, we identified nine Rab GTPase and kinase genes that modulated aSyn aggregation, toxicity and levels. From those, Rab8b, Rab11a, Rab13 and Slp5 were able to promote the clearance of aSyn inclusions and rescue aSyn induced toxicity. Furthermore, we found that endocytic recycling and secretion of aSyn was enhanced upon Rab11a and Rab13 expression in cells accumulating aSyn inclusions. Overall, our study resulted in the identification of new molecular players involved in the aggregation, toxicity, and secretion of aSyn, opening novel avenues for our understanding of the molecular basis of synucleinopathies.